Optimization of Health Workers in The Implementation of Provider Initiated HIV Testing and Counseling (PITC) - Hikmah, Faiqatul; Fernandes, Angelina da Costa; Karimah, Rinda Nurul; Suandana, Iwan Abdi; Susindra, Yoswenita (International Journal of Health and Information System, 2024)
Background: Provider Initiated HIV Testing and Counseling (PITC) is a service offering HIV testing by health workers to all patients in health facilities1. The quality of PITC services that do not meet standards is still a problem, thus becoming an obstacle to PITC services. This causes PITC user satisfaction to be low. The aim of this research is to determine efforts to optimize health workers in the implementation of provider-initiated HIV testing and counseling (PITC). This systematic research was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method to assess, review and synthesize research. Search through the database by entering the keywords "HIV", "HIV test", "Provider initiated HIV testing and counseling" "PITC", on PubMed, Science Direct, ProQuest. 9 research journals were selected after going through specified stages. Barriers for health workers are high workload, lack of human resources and not all health workers are trained in PITC. Optimizing PITC services in health care settings cannot stand alone, health services that are integrated with other health services require the ability of health workers to be able to offer HIV tests to patients. Optimizing human resources in the health sector can be done by increasing the ability of health workers to carry out PITC through good education and training. The complete implementation of PITC starting from the pretest and posttest will emphasize changes in patient behavior to improve their health status.